Pengembangan Leaflet Berbasis Android sebagai Penunjang Bahan Ajar Pada Mata Pelajaran OTK Sarana dan Prasarana Kelas XI OTKP di SMK PGRI 2 Sidoarjo - Nelly Meiristanti; Durinta Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study is to describe the development process, analyze the feasibility, and analyze student responses to android-based leaflets as supporting teaching materials in OTK Facilities and Infrastructure XI OTKP class subjects at SMK PGRI 2 Sidoarjo. This type of research is R & D research, while the development model used is the 4D development model from Thiagarajan, namely: Define, Design, Develop and Disseminate. The subjects in this study were 20 students of class XI OTKP 1 at SMK PGRI 2 Sidoarjo. The research instruments used included study sheets and validation by material experts, linguists, graphic experts and student response questionnaires. The results showed that the results of the study and validation of android-based leaflets based on the aspect of material eligibility obtained a percentage of 93% with a very strong category, linguistic aspects obtained a percentage of 98% with a very strong category, the aspect of graphics obtained a percentage of 92% with a very strong category. Based on the results of a limited trial to 20 students of class XI OTKP 1 on android-based leaflets get a percentage of 99% with a very strong category. So it can be concluded that the Android-based leaflet as a support for teaching materials in OTK Facilities and Infrastructure class XI OTKP 1 which has been developed is suitable for the learning process.Keywords: android, leaflet, teaching materials.